2023
DOI: 10.3390/molecules28041734
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Obesity and Anti-Steatotic Effects of Chrysin in a Rat Model of Obesity Mediated through Modulating the Hepatic AMPK/mTOR/lipogenesis Pathways

Abstract: Background: Obesity is a complex multifactorial disease characterized by excessive adiposity, and is linked to an increased risk of nonalcoholic fatty liver disease (NAFLD). Flavonoids are natural polyphenolic compounds that exert interesting pharmacological effects as antioxidant, anti-inflammatory, and lipid-lowering agents. In the present study, we investigated the possible therapeutic effects of the flavonoid chrysin on obesity and NAFLD in rats, and the role of AMP-activated protein kinase (AMPK)/mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Obesity is associated with reduced AMPK activation, concomitant with alterations in glycolysis, insulin sensitivity, hepatic lipid metabolism and inflammation 39 . Oriquat et al, 2023 showed that HFD induced significant downregulation of the expression of AMPK and its upstream activating kinase (LKB1), and p-AMPK and LKB1 protein levels 40 . The role of AMPK in ovarian maturation was confirmed in the present study by the correlation data which indicated that AMPK showed a positive correlation with the number of primordial, primary, and antral follicles and negatively correlated with the number of cystic follicles and histologic lesion score.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with reduced AMPK activation, concomitant with alterations in glycolysis, insulin sensitivity, hepatic lipid metabolism and inflammation 39 . Oriquat et al, 2023 showed that HFD induced significant downregulation of the expression of AMPK and its upstream activating kinase (LKB1), and p-AMPK and LKB1 protein levels 40 . The role of AMPK in ovarian maturation was confirmed in the present study by the correlation data which indicated that AMPK showed a positive correlation with the number of primordial, primary, and antral follicles and negatively correlated with the number of cystic follicles and histologic lesion score.…”
Section: Discussionmentioning
confidence: 99%
“…In a parallel manner, a 4-week regimen of chrysin treatment in rats successfully reversed glucose elevation, inflammation, and the decline in serum insulin levels associated with aging, indicating that chrysin helps preserve islet function [ 248 ]. The research conducted by Oriquat et al revealed that chrysin exhibited notable effects in mitigating weight gain and rectifying hyperglycemia, insulin resistance, and dyslipidemia while simultaneously improving adipocytokine levels in rats with metabolic disturbances induced by a high-fat diet [ 249 ]. Moreover, the authors provided evidence that chrysin regulates hepatic signaling by activating the AMPK pathway and inhibiting the mTOR and lipogenic pathways, resulting in anti-obesity and antisteatotic effects [ 249 ].…”
Section: Nutrient-sensing Pathwaysmentioning
confidence: 99%
“…The research conducted by Oriquat et al revealed that chrysin exhibited notable effects in mitigating weight gain and rectifying hyperglycemia, insulin resistance, and dyslipidemia while simultaneously improving adipocytokine levels in rats with metabolic disturbances induced by a high-fat diet [ 249 ]. Moreover, the authors provided evidence that chrysin regulates hepatic signaling by activating the AMPK pathway and inhibiting the mTOR and lipogenic pathways, resulting in anti-obesity and antisteatotic effects [ 249 ]. The prevalence of nonalcoholic fatty liver disease (NAFLD) is 39% among individuals aged 40 to 50 and exceeds 40% in those aged 70 and above [ 250 ].…”
Section: Nutrient-sensing Pathwaysmentioning
confidence: 99%
“…It has been recently reported that natural products, including phenols, flavonoids, glycosides, quinones, terpenoids, pyrazines, alkaloids, and phenylpropanoids, have antioxidant, energy-producing, anti-inflammatory, anti-apoptotic, and anti-aging effects, which mainly influence the AMPK/Nrf2/mTOR, Nrf2/HO-1, NAMPT/NAD(+)/SIRT, AMPK/SIRT1/PGC-1alpha and PKCs/PARPs/NF-kB signaling pathways, thereby regulating NAD(+) metabolism to prevent and treat NAFLD [ 117 ]. Hepatoprotective effects, caused by the inhibition of PI3K/Akt/mTOR signaling and effective alleviation of oxidative stress damage and ER stress induced by excessive lipid accumulation in hepatocytes, and activation of autophagy were observed for agonists of AMPK thymoquinone [ 118 ] and 5-aminoimidazole-4-carboxamide-1-beta-D-ribofuranoside (AICAR) [ 119 ], agonist of GLP-1/glucagon cotadutide [ 120 ], an antagonist of sphingosine 1-phosphate receptor 2 (S1PR2) JTE-013 [ 26 ], activator of PI3K, autophagy-related genes (ATG) and agonist of Nrf2, PPARα and hemeoxygenase-1 (HO-1) pterostilbene [ 121 ], flavonoid with antioxidant properties involving CYP7A1, quercetin [ 122 ], Pueraria flavonoids [ 92 ], a novel gerotherapy compound, BIOIO-1001 [ 123 ], a natural nonenzymatic antioxidant with low toxicity schisandrin B (Sch B) [ 124 ], H1-antihistamines (AHs) [ 125 ], fat soluble polyphenol Tanshinone IIA (TsIIA) [ 126 ], purendan (PRD) [ 127 ], down-regulating the expression of p-mTOR, p-S6K1 and SREBP-1c, chrysin [ 128 ], red pepper seed extract (RPS) [ 129 ], Gardenia Fructus (GF) extracts [ 130 ], curcumin [ 131 ], and magnesium [ 132 ].…”
Section: New Therapeutic Approaches and Molecular Targets In Nafld/na...mentioning
confidence: 99%